Efectos de la aplicación de "jigsaw" sobre la adquisición de competencias en dirección de operaciones - Cristina López; Juan C. Real (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– The aim of this study was to determine the effects of the cooperative ``jigsaw'' method on generic competence-based training by university students. This specifically sought to understand how systemic, instrumental and interpersonal competences are more easily acquired by adopting ``jigsaw'' in the teaching-learning procedure. The results reveal that this cooperative learning method makes the development of systemic and instrumental competences easier to a greater extent than interpersonal ones. Meta-reflection or progressive rote learning achieved a highest score among systemic competences. Focusing our attention on the instrumental dimension, peer interaction, students' communication skills, participation, resolution of peer conflicts and direct instruction, these competences sty out from the rest. Finally, responsibility was the easiest competence in the interpersonal dimension.
Keywords: A22; M11; 330; cooperative learning; generic competences; "jigsaw"; high-level education; descriptive statistics